Europhile Public vs Eurosceptic Governing Elite in Hungary? - Borbála Göncz; György Lengyel (Intereconomics, 2021)
The threat of an epidemic narrows the scope for political competition. As Fidesz's position within the EU has weakened significantly with the withdrawal from the European People's Party, and the COVID-19 crisis is generating serious social tensions, the questions seem to be more open in the spring of 2022 than during the previous three elections.
Keywords: 330; Europäische Integration; EU-Staaten; Ungarn